Toddlers, Parents, and Culture 2018
DOI: 10.4324/9781315203713-2
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of the Joint Effort Toddler Temperament Consortium (JETTC)

Abstract: Researchers at all sites recruited samples of about 50 families of toddlers who were roughly between 18 and 36 months of age. A total of 865 families were recruited, although only the 853 indicating the sex of their child were included in analyses. Only one child was selected per family, and children with clinical diagnoses were excluded. For all but two countries, data were collected in a single site. In the Netherlands and the United States (US), data from two locations were combined. Our recruitment approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…JETTC sites were selected to capture a wide range of geographic regions with meaningful variability in cultural orientation (e.g., individualism versus collectivism) and culturally driven parenting practices. These were also sites where investigators were using Rothbart temperament instruments, thus translation efforts had already been undertaken and relationships required for data collection established (for further details on the JETTC sites please see Chapter 2 Putnam et al (2018) ). Across the JETTC sites (i.e., Belgium, Brazil, Chile, China, Finland, Italy, Mexico, Netherlands, Romania, Russia, Spain, South Korea, Turkey, United States), mean enrollment was 61 families, ranging from a low of 49 families in Chile to a high of 119 families in the Netherlands ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…JETTC sites were selected to capture a wide range of geographic regions with meaningful variability in cultural orientation (e.g., individualism versus collectivism) and culturally driven parenting practices. These were also sites where investigators were using Rothbart temperament instruments, thus translation efforts had already been undertaken and relationships required for data collection established (for further details on the JETTC sites please see Chapter 2 Putnam et al (2018) ). Across the JETTC sites (i.e., Belgium, Brazil, Chile, China, Finland, Italy, Mexico, Netherlands, Romania, Russia, Spain, South Korea, Turkey, United States), mean enrollment was 61 families, ranging from a low of 49 families in Chile to a high of 119 families in the Netherlands ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the ECBQ development paper ( Putnam et al, 2006 ), this measure demonstrated moderate interrater reliability, longitudinal stability at a moderate to large level from the ages of six to 36 months, and adequate internal consistency. Regarding construct validity, studies have consistently found relations between ECBQ indicators and temperament scores obtained in infancy and childhood ( Putnam et al, 2018 ), as well as behavior problems ( Gartstein et al, 2012 ), including in countries other than the United States ( Gonzalez-Salinas et al, 2018 ). A study examining the Japanese version of the ECBQ further demonstrated that the measure showed internal consistency across its 18 scales and remained consistent across time (i.e., 18–36 months; Sukigara et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table adapted with permission from (Putnam et al, 2018). Although links between TV viewing and regulation in clinical populations are important to consider, related research questions were beyond the scope of the current investigation.…”
Section: Participantsmentioning
confidence: 99%